Bioprinting of microalgae laden scaffold for tissue regeneration - Yerlikaya, Davut; Inan, Benan; Balkanli, Didem (SPRINGER, 2025)
In recent years, microalgae that can be a continuous source of oxygen for cells and rich in bioactive compounds, have been used as an innovative approach to prevent hypoxia after implantation of biomaterials. Oxygen can be provided photosynthetically by the polar microalga (Chlorella variabilis) in combination with human cells, even without an external oxygen source. In this study, 3D bioprinting of microalgae laden scaffolds was investigated and characterized before use in wound healing. Prepared bioink consisted of alginate and different ratios of collagen (5, 10 and 15%) and C. variabilis cells. Printing was carried out at 10 mm s-1 and the pressure was 50 kPa. Each sample had 0.6-0.7 mL volume and 6-7 x 105 cells. After the 3D bioprinting process, scaffolds were crosslinked with 100 mM calcium chloride for 10 min and incubated. It was observed that the microalgae grew well over 6 days in the scaffold. Also, an oxygen increase from 6 to 12 mg L-1 was determined. It was demonstrated that, development of microalgae-laden scaffolds is promising on the delivery of oxygen or bioactive compounds as therapeutic agents.
Keywords: Bioprinting; Microalgae; Biomaterials; Tissue engineering; 3D-plotted hydrogel; Chlorophyta; PHOTOSYNTHETIC BIOMATERIALS; TEMPERATURE; VIABILITY; Biotechnology & Applied Microbiology; Marine & Freshwater Biology